Asymmetric information, adverse selection, and the pricing of CMBS☆ - An, Xudong; Deng, Yongheng; Gabriel, Stuart A. (Journal of Financial Economics, 2011)
We demonstrate that asymmetric information between sellers (loan originators) and purchasers (investors and securities issuers) of commercial mortgages gives rise to a standard lemons problem, whereby portfolio lenders use private information to liquidate lower quality loans in commercial mortgage-backed securities (CMBS) markets. Conduit lenders, who originate loans for direct sale into securitization markets, mitigate problems of asymmetric information and adverse selection in loan sales. Our theory provides an explanation for the pricing puzzle observed in CMBS markets, whereby conduit CMBS loans are priced higher than portfolio loans, despite widespread belief that conduit loans are originated at lower quality. Consistent with theoretical predictions of a lemons discount, our empirical analysis of 141 CMBS deals and 16,760 CMBS loans shows that, after controlling for observable determinants of loan pricing, conduit loans enjoyed a 34 basis points pricing advantage over portfolio loans in the CMBS market.